Internet Users and Basic Concepts of Consumer Behavior - Sholehuddin Sholehuddin; Moh. Karim (Interkoneksi: Journal of Computer Science and Digital Business, 2026)
Advancements in information technology have significantly influenced consumer behavior, particularly regarding the use of the internet to access information, conduct transactions, and make purchasing decisions. This study aims to examine the characteristics of internet usage, fundamental concepts of consumer behavior, the purchasing decision-making process, and the key technologies supporting online marketing. A library research method was employed, utilizing a qualitative descriptive approach through a review of books, scholarly journals, and articles. Data were analyzed using content analysis to identify theoretical connections and develop a comprehensive understanding. The findings indicate that internet users exhibit specific characteristics, such as network access, technological proficiency, social interaction, digital content consumption, and security awareness. Consumer behavior is shaped by evolving needs and desires, which in turn influence purchasing decisions across stages ranging from need recognition, information search, and alternative evaluation to post-purchase behavior. Furthermore, the success of online marketing is heavily influenced by digital technologies—such as websites and CMS, social media, e-commerce, SEO/SEM, email marketing, web analytics, mobile applications, and AI/chatbots. The study underscores the importance of understanding consumer behavior in conjunction with the use of digital technology to ensure online marketing strategies are effective, efficient, and capable of enhancing customer satisfaction.